2020
DOI: 10.1021/jacs.0c09072
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Diffusion of Photoswitchable Receptors by Binding Anti-electrostatic Hydrogen-Bonded Phosphate Oligomers

Abstract: Dihydrogen phosphate anions are found to spontaneously associate into anti-electrostatic oligomers via hydrogen bonding interactions at millimolar concentrations in DMSO. Diffusion NMR measurements supported formation of these oligomers, which can be bound by photoswitchable anion receptors to form large bridged assemblies of approximately three times the volume of the unbound receptor. Photoisomerization of the oligomer-bound receptor causes a decrease in diffusion coefficient of up to 16%, corresponding to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 103 publications
0
32
0
Order By: Relevance
“…The classical description of hydrogen bonds invokes an electrostatic Yδ- Hδ+ −Xδ- interaction which would become a destabilizing Yδ- Xδ- −Hδ+ factor in the non conventional cases. Weinhold and Klein [72] reported for the first time anti‐electrostatic hydrogen bonds and showed that orbital interactions more than compensate for the local Coulomb repulsion, other studies soon followed [73–76] . For the particular case of the Alanine dimers, in the φdφa NBO orbital interaction picture, it is the π * C=O orbital that acts as the acceptor of charge for most of the non conventional contacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical description of hydrogen bonds invokes an electrostatic Yδ- Hδ+ −Xδ- interaction which would become a destabilizing Yδ- Xδ- −Hδ+ factor in the non conventional cases. Weinhold and Klein [72] reported for the first time anti‐electrostatic hydrogen bonds and showed that orbital interactions more than compensate for the local Coulomb repulsion, other studies soon followed [73–76] . For the particular case of the Alanine dimers, in the φdφa NBO orbital interaction picture, it is the π * C=O orbital that acts as the acceptor of charge for most of the non conventional contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Weinhold and Klein [72] reported for the first time antielectrostatic hydrogen bonds and showed that orbital interactions more than compensate for the local Coulomb repulsion, other studies soon followed. [73][74][75][76] For the particular case of the Alanine dimers, in the � d ! � a NBO orbital interaction picture, it is the π* C=O orbital that acts as the acceptor of charge for most of the non conventional contacts.…”
Section: Non Conventional or Exotic Contactsmentioning
confidence: 99%
“…Nonetheless, this intuitive idea has been countered by a growing number of observations, from both experimental and theoretical quarters, that like-charged ions can engage in H-bonds with one another under certain conditions. Examples of such bonds involve H 2 PO 4 − , 12–15 (RPO 3 H − ), 16 HSO 4 − , 17,18 HCO 3 − , 19,20 carboxylates, 21,22 and aspartate, 23 as well as an assortment of others. 24–29…”
Section: Introductionmentioning
confidence: 99%
“…Flood and co‐workers have taken this concept further by using UV light to sequester a wide range of anions, controlling the size of the helical quaternary structure and function by anion binding through azo −N=N− bonds installed on the foldamer [9a,b] . Other groups have been able to photoisomerize stiff‐stilbene oligomer scaffolds decorated with urea anion‐binding motifs to form weakly binding E forms and strongly binding Z forms with dihydrogenphosphate using near‐UV light, with moderate photoconversion ratios [12] . Aside from bioinspired receptors, an acylhydrazone‐based photoswitch with two separate binding sites for cations and anions has been reported; along with a multistep synthesis, cations Li + , Na + , K + , and Bu 4 N + and anions Ph 4 B − , Cl − , Br − , and I − were studied, revealing limited selectivity between cation and anion combinations [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Aside from bioinspired receptors, an acylhydrazone‐based photoswitch with two separate binding sites for cations and anions has been reported; along with a multistep synthesis, cations Li + , Na + , K + , and Bu 4 N + and anions Ph 4 B − , Cl − , Br − , and I − were studied, revealing limited selectivity between cation and anion combinations [13] . Notable photoswitchable systems by Feringa and co‐workers incorporate the photoactive stiff‐stillbene group to effect a conformational switch with light, while urea groups participate in binding [12,14] . This general framework and its analogs have been used to study a wide range of anions including Cl − , Br − , NO 3 − , CH 3 CO 2 − , H 2 PO 4 − , and HSO 4 − with maximum binding constants of 7.5×10 3 M −1 for H 2 PO 4 − in DMSO.…”
Section: Introductionmentioning
confidence: 99%